(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article covers information about the evacuation of starving and orphaned children from some regions of the USSR to the territory of the USSR in the 20s and 40s of the 20th centuries, the establishment of “Children’s Homes” for their accommodation, and the assistance of our hospitable and tolerant people to the children who moved. Also, with the help of archival sources and scientific literature, the causes and consequences of this evacuation policy implemented by the Soviets, as well as the state of aid and work done by the state and the government for the displaced children are described.